Ways to Improve the Lubricating Properties of Greases (Texas Journal of Engineering and Technology, 2022)
The article analyzes the conditions of use and the main characteristics of greases. Taking into account the ability to form a strong film on the metal surface and a wide range of operating temperature, we conducted a number of experiments using molybdenum disulfide in laboratory conditions. The study shows that the use of molybdenum disulfide MoS2 additives to greases reduces the wear of parts, increases the service life of friction units and reduces the likelihood of high-loaded parts being bullied and elasticity at low temperatures.